Antipsychotic long-acting injections - Haddad, Peter M.; Lambert, Tim, 1955-; Lauriello, John. (Oxford : Oxford University Press, 2011)
Antipsychotic long-acting injections (LAIs) were introduced in the 1960s to improve treatment adherence in schizophrenia. This book brings together clinical and research findings on second generation LAIs in a comprehensive volume with chapters written by international experts.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Antipsychotic drugs -- Controlled release; Injections